BANGKITAN SIMTOMATIK AKUT: INSIDENSI, ETIOLOGI, DAN MORTALITAS PASIEN RSUD GUNUNGSITOLI TAHUN 2015–2019 - Stefanus Erdana Putra; Berkat Hia; Muhammad Hafizhan; Fauzi Novia; Isnaening Tyas; Astrida Fesky Febrianty (PERDOSNI, 2021)
Introduction: Acute symptomatic seizures are seizures that occur due to acute disorders of the central nervoussystem due to structural, infectious, inflammatory, and metabolic disorders. Acute symptomatic seizures and unprovokedseizures must be distinguished because they have different prognoses. Aim: To determine the incidence, etiology, and prognosis of acute symptomatic seizure patients treated inGunungsitoli Regional General Hospital during 2015-2019. Methods: This was a cross-sectional study in patients with acute symptomatic seizure in Gunungsitoli RegionalGeneral Hospital Nias District during 2015-2019. Data were obtained from the medical record in Gunungsitoli RegionalGeneral Hospital. Multiple logistic regression analysis was used to calculate odds ratios (ORs) of age for mortality. Results: There were 88 acute symptomatic seizure patients with a proportional comparison between males andfemales (1.1:1). The most prevalent encountered etiology of acute symptomatic seizure patients was metabolic disorders(51.14%) consisting of 25% uremia; 5.68% hyponatremia; 4.54% hyperglycemia; 6.83% hepatic; and 9.09% hypoglycemiawith a case fatality rate of 29.55%. Discussion: Characteristics of acute symptomatic seizures patients treated in Gunungsitoli Regional GeneralHospital were not affected by gender, with the most often encountered etiology was metabolic disorders. Keyword: Acute symptomatic seizure